Islam and the transformation of culture - "Hanifi, M. Jamil" (Bombay, 1974)
The object of this book is to provide the reader with an analysis of Islam and Islamic Law and their evolution,along with their potentiality for "technicization," with particular reference to the Turkish transformation whose beginning goes back as far as the early part of the eighteenth century.A study of this transformation and the model proposed may contribute to an understanding of contemporary conditions in many Muslim countries; but apart from this,it will be helpful to those who are interested in the comparative study of law, politics,and the religious transformation in non-Western ,Muslim societies.
Keywords: Islam and social problems